Gastroprotective mechanisms of Citrus lemon (Rutaceae) essential oil and its majority compounds limonene and beta-pinene: Involvement of heat-shock protein-70, vasoactive intestinal peptide, glutathione, sulfhydryl compounds, nitric oxide and prostaglandin E-2 - Rozza, Ariane Leite [UNESP]; Moraes, Thiago de Mello [UNESP]; Kushima, Helio [UNESP]; Tanimoto, Alexandre [UNESP]; Mayo Marques, Marcia Ortiz; Bauab, Taís Maria [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP]; Pellizzon, Claudia Helena [UNESP] (Elsevier B.V., 2011)
Citrus lemon (CL) belongs to Rutaceae family and is popularly known in Brazil as lima() siciliano. The phytochemical analysis of CL fruit bark essential oil showed two majority components, limonene (LIM) and beta-pinene (PIN). This study aimed to evaluate the gastroprotective mechanism of action from CL, LIM and PIN in ethanol- and indomethacin-induced gastric ulcers and its in vitro anti-Helicobacter pylori activity. After ethanol-induced gastric ulcer, the ulcer area was measured and the stomachs were destined to histology (HE and PAS), immunohistochemistry for HSP-70 and VIP and glutathione (GSH) measurement. The involvement of nitric oxide (NO) and sulfhydryl (SH) compounds was determined. The ulcer area for indomethacin-induced gastric ulcers was measured. PGE(2) concentration was biochemically measured. The minimum inhibitory concentration (MIC) against H. pylori was determined in vitro. In ethanol model. CL and LIM demonstrated 100% of gastroprotection, while PIN did not exert effective gastroprotection (53.26%). In the indomethacin model, CL and LIM offered effective gastroprotection but PIN did not show gastroprotective effect. The gastric ulcer area of rats pretreated with NO-synthase inhibitor or SH-blocker was decreased in comparison to the control group. The MIC obtained for CL was 125 mu g/mL, for LIM was 75 mu g/mL and for PIN was 500 mu g/mL. The gastroprotective effect of CL and LIM was involved with increasing in mucus secretion, HSP-70 and VIP, but not with GSH. NO or SH compounds. CL gastroprotective mechanism is involved with PGE(2). PIN did not present gastroprotective activity. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Citrus lemon essential oil; Limonene; Gastroprotection; PGE(2); Sulfhydryl compounds